Absence of Clinically Relevant Interactions between Rivaroxaban - an Oral, Direct Factor Xa Inhibitor - and Digoxin or Atorvastatin in Healthy Subjects - Kubitza, D; Becka, M; Roth, A; Mueck, W (Journal of international medical research, 2012)
Objective: To investigate potential interactions between rivaroxaban, an oral direct Factor Xa inhibitor approved for the management of thromboembolic disorders, and digoxin or atorvastatin. Methods: Two randomized, phase 1 clinical trials were undertaken in healthy men to assess pharmacokinetic and pharmacodynamic interactions between rivaroxaban and digoxin or atorvastatin, and the safety of these drug combinations. Results: Steady-state rivaroxaban did not affect the pharmacokinetic profile of steady-state digoxin (n = 17). Digoxin did not significantly influence the pharmacokinetic profile of single-dose rivaroxaban and had minimal effects on rivaroxaban-induced inhibition of Factor Xa activity and prolongation of clotting time. Similarly, steady-state atorvastatin did not affect the pharmacokinetic profile or the pharmacodynamics of rivaroxaban and vice versa (n = 19). All drugs (alone or in combination) were well tolerated. Conclusions: There were no clinically relevant pharmacokinetic or pharmaco - dynamic interactions between rivaroxaban and digoxin, or between rivaroxaban and atorvastatin, suggesting that rivaroxaban can be coadministered with either drug. This study also confirmed that rivaroxaban does not interact with substrates for permeability (P)-glycoprotein alone (digoxin) or P-glycoprotein and cytochrome P450(CYP)3A4 (atorvastatin).